2018
DOI: 10.1128/mbio.01056-18
|View full text |Cite
|
Sign up to set email alerts
|

New Variant of Multidrug-Resistant Salmonella enterica Serovar Typhimurium Associated with Invasive Disease in Immunocompromised Patients in Vietnam

Abstract: Salmonella Typhimurium is a major diarrheal pathogen and associated with invasive nontyphoid Salmonella (iNTS) disease in vulnerable populations. We present the first characterization of iNTS organisms in Southeast Asia and describe a different evolutionary trajectory from that of organisms causing iNTS in sub-Saharan Africa. In Vietnam, the globally distributed monophasic variant of Salmonella Typhimurium, the serovar I:4,[5],12:i:− ST34 clone, has reacquired a phase 2 flagellum and gained a multidrug-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 39 publications
8
87
2
Order By: Relevance
“…Indeed some β subclades such as those associated with the DT56, DT2 and DT8 complexes that are well characterized host adapted clonal groups 11,12,21 , contained exclusively isolates from avian species, and were present on relatively extended internal branches. This general phylogenetic topology is consistent with that described for distinct collections of S. Typhimurium strains from North America and Asia 36,37 .…”
Section: Discussionsupporting
confidence: 88%
“…Indeed some β subclades such as those associated with the DT56, DT2 and DT8 complexes that are well characterized host adapted clonal groups 11,12,21 , contained exclusively isolates from avian species, and were present on relatively extended internal branches. This general phylogenetic topology is consistent with that described for distinct collections of S. Typhimurium strains from North America and Asia 36,37 .…”
Section: Discussionsupporting
confidence: 88%
“…The most invasive serovars from England (S. Poona, S. Panama, and S. Dublin) have also been noted in other developed countries, like the United States and Australia (4,26). We found that S. Typhimurium was not the most invasive serovar in England, which is very different from other countries and regions, such as Australia, South East Asia, and sub-Saharan Africa, where invasive S. Typhimurium predominates (26)(27)(28).…”
Section: Discussioncontrasting
confidence: 49%
“…During the past decade, blaCTX-M-55 has been increasingly found in Enterobacteriaceae isolated from humans, animals, and the environment (36). Recently, mcr genes were found in Salmonella Typhimurium/4, [5],12:i:-ST34 isolated from humans and swine in North America, Europe, Australia, and Asian countries other than Japan (8,11,34,37,38). The present study is the first to identify mcr-1, mcr-3, mcr-5, and/or mcr-9 in Salmonella 4, [5],12:i:-ST34 disseminated into food animals in Japan.…”
Section: Acquisition Of Amr In Clade 9 Strainsmentioning
confidence: 99%
“…Salmonella 4, [5],12:i:-infections have been increasingly occurring in European countries since the 2000s and have since spread to the United States, South America, Australia, and Asia (3)(4)(5)(6)(7)(8)(9). A European clone is one of the best studied Salmonella 4, [5],12:i:isolates because of its rapid and worldwide dissemination (6,(9)(10)(11). Swine was reported as the main reservoir of this clone, and the contaminated products are considered causative agents of food-borne infection (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation